Palinomorfos ante-cenomanianos do «Grés do Buçaco» (Lousã, Portugal) - Trincão, P. (1989)
The palynological study of sediments from lower levels of Lousã basin (Lomba do Alveite Arkoses), is presented. The palynological association includes several species of Appendicisporites and Cicatricosisporites, Costatoperforosporites sp., Ischyosporites teixeirae, Pattelasporites tavaredensis, Echinatisporis sp., Spheripollenites perinatus, Tricolpopollenites sp. and Retitricolpites maximus. The presence of the last two forms; and the absence of Normapolles, suggest an ante-Cenomanian, most probably Albian age for the assemblage. From these results, the begining of the infilling of the Lousã basin, is, at least in part, synchronous with the deposition of the «Grés Grosseiro Inferior» from the Occidental portuguese Basin. The presence of Lower Cretaceous Basin, is shown for the first time.